Speaking Problems in Vocational High School - Hervinna Febriani Sitorus; Putri Vaniarisa Sinaga; Syntia Devi Lumban Gaol; Rosalina Imelda Octaviana Situmorang; Selviana Napitupulu (Ilmu Inovasi Nusantara, 2022)
This study aims to find the difficulties when speaking English which are mostly faced by vocational students. This study used qualitative research methods. This research instrument is observation and interviews. Based on the results of the observation and interviews, it was found that students found speaking difficulties like (1) pause, (2) fillers, (3) mental problems, (4) lack of ideas, (5) grammatical error, (6) poor vocabulary. Speaking skill is very important for us because serves to maintain and establish social relations, and the transactional functions, which focus on the exchange of the informations. Therefore, it is necessary to conduct research to solve the problem of speaking difficulties experienced by students, so that there are improvements for the future and students' speaking skills are increasing